Preparation method of anti-slip and anti-fouling ceramic tile and ceramic tile product thereof
By accurately controlling the particle grading of anti-slip particles and the fineness of transparent glaze slurry, a consistent anti-slip texture is formed, which solves the problem of unstable anti-slip performance of existing anti-slip ceramic tiles, and realizes efficient anti-slip and anti-slip of ceramic tiles. performance.
Patent Information
- Application Number
- CN202411505788.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The anti-slip performance of existing anti-slip ceramic tiles is unstable, resulting in large differences in the anti-slip effects of different batches of products, and cannot provide sufficient safety guarantees.
By accurately controlling the particle grading of anti-slip particles, the proportion of coarse and fine particles in the anti-slip particles produced in different batches is stable. Combined with the fineness control of transparent glaze slurry, a consistent anti-slip texture is formed and ceramic tiles are improved. Anti-slip performance.
The anti-slip performance consistency and stability of ceramic tile products is achieved, greatly improving the anti-slip safety performance of the product, and enhancing the anti-slip and easy-to-clean performance.
Smart Images

Figure CN119390479A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, in particular to a method for preparing a non-slip and anti-fouling ceramic tile and a ceramic tile product thereof. Background Art
[0002] Anti-slip ceramic tiles are a type of ceramic product with a special surface treatment. Their purpose is to prevent users from slipping when walking in a humid or slippery environment, providing users with a safer living environment.
[0003] The Chinese invention patent with application number 201310605534.2 and titled “A Ceramic Tile with a Dry Particle Glaze Decorative Surface and Its Manufacturing Method” discloses a method of applying a dry particle layer on the surface of a ceramic tile, wherein the dry particle layer is composed of dry particles with a sieve size of -60 to -120 mesh, so as to increase the friction coefficient of the ceramic tile surface and make the ceramic tile have an anti-slip effect. However, it was found during use that in this technology, since the particle size of the dry particles is not further refined and controlled, the proportion of coarse particles and fine particles in the dry particles produced in different batches varies greatly, so that the anti-slip textures generated by different batches of dry particles on the surface of the ceramic tile also vary greatly, and the anti-slip performance of the ceramic tile is unstable, which greatly reduces the anti-slip safety performance of the ceramic tile and cannot provide users with a very strong safety guarantee. Summary of the invention
[0004] The purpose of the present invention is to solve the above-mentioned problems and shortcomings, and to provide a method for preparing anti-slip and anti-fouling ceramic tiles. By accurately controlling the fineness grading of the anti-slip particles, the proportion of coarse particles and fine particles in the anti-slip particles produced in different batches is stabilized, thereby making the anti-slip texture formed by the anti-slip particles on the surface of the ceramic tile product have a consistent distribution; the ceramic tile product prepared by this method has excellent anti-slip performance, ensures the quality of the product, and greatly improves the anti-slip safety performance of the ceramic tile product.
[0005] The technical solution of the present invention is achieved in this way:
[0006] A method for preparing anti-skid and anti-fouling ceramic tiles, comprising mixing anti-skid particles with transparent glaze slurry to form an anti-skid glaze, and then applying the anti-skid glaze to the surface of a ceramic tile body, wherein the ball-milling fineness of the transparent glaze slurry is 0.3% to 0.5% by weight of the residue on a 325-mesh sieve, and the particle grading of the anti-skid particles is calculated as follows in weight percentage: less than 0.5% on an 80-mesh sieve, 30% to 35% on a 100-mesh sieve, 75% to 80% on a 120-mesh sieve, and 95% to 98% on a 250-mesh sieve.
[0007] Furthermore, the amount of the anti-slip particles added to the transparent glaze slurry is 12% to 20% by weight.
[0008] Furthermore, the chemical composition of the transparent glaze slurry is calculated in weight percentage as follows: Al2O3 content 16% to 25%, SiO2 content 45% to 55%, CaO content 3% to 8%, MgO content 1% to 2%, ZnO content 2% to 3%, BaO content 2% to 4%, K2O content 1% to 2%, Na2O content 6% to 12%, and loss on ignition 8% to 13%.
[0009] Furthermore, the chemical composition of the anti-slip particles is calculated in weight percentage as follows: Al2O3 content 8% to 18%, SiO2 content 50% to 65%, CaO content 6% to 18%, MgO content 5% to 12%, ZnO content 2% to 5%, BaO content 4% to 10%, K2O content 5% to 10%; the melting temperature of the anti-slip particles is greater than or equal to 1200°C.
[0010] Furthermore, the usage amount of the anti-slip glaze slurry on the ceramic tile body is 63-72 g / ㎡.
[0011] Furthermore, the chemical composition of the ceramic tile body is calculated in weight percentage as follows: Al2O3 content is 18% to 21%, SiO2 content is 60% to 74%, CaO content is 0.1% to 0.5%, MgO content is 0.7% to 1.4%, Fe2O3 content is 0.3% to 0.7%, TiO2 content is 0.1% to 0.5%, K2O content is 1% to 3%, and Na2O content is 2% to 4%.
[0012] Furthermore, the particle size distribution of the powder obtained by powder spraying after the ball milling slurry is as follows: less than 0.5% of the material on the 20-mesh sieve, and 70% to 85% of the material on the 60-mesh sieve, in terms of weight percentage.
[0013] Furthermore, the powder is fed into a press and pressed into a ceramic tile body, the pressing pressure of the press is 310±10 bar, and the number of single-machine pressings is 3.5 to 4.0 times per minute; the dry strength of the obtained ceramic tile body is greater than 0.8 MPa.
[0014] Furthermore, the ceramic tile body with anti-slip glaze applied on the surface is sent to the kiln for firing, using a one-time firing process and a firing time of 45 to 55 minutes; the firing curve is: the first stage is from room temperature to 900°C, and the heating time is 5 to 10 minutes; the second stage is from 900°C to 1200°C, and the heating time is 13 to 17 minutes; then it is kept at 1200°C for 10 to 15 minutes; after the insulation is completed, it is cooled from 1200°C to 900°C, and the cooling time is 2 to 3 minutes; then it is cooled from 900°C to room temperature, and the cooling time is 5 to 10 minutes.
[0015] The present invention also provides a ceramic tile product prepared by the above-mentioned preparation method, which is characterized in that it includes a green body and an anti-skid and anti-fouling layer located on the surface of the green body, the anti-skid and anti-fouling layer has an anti-slip performance greater than or equal to R11, a wet static friction coefficient greater than or equal to 0.78, a wet anti-slip value greater than or equal to 60, and a stain resistance level greater than or equal to 5.
[0016] The beneficial effects of the present invention: the preparation method of the anti-slip and anti-fouling ceramic tiles provided in the present application, by accurately controlling the particle grading of the anti-slip particles, makes the proportion of coarse particles and fine particles in each batch of anti-slip particles produced very stable, so that when the anti-slip particles are combined with the transparent glaze and fired, the size distribution of the anti-slip concave-convex texture formed on the surface of the ceramic tile product remains consistent, so that the anti-slip performance of the ceramic tile products produced in each batch remains consistent and can have very excellent anti-slip performance, which greatly guarantees the anti-slip quality of the ceramic tile products, provides users with a strong anti-slip safety guarantee, and thus greatly improves customer recognition. Compared with the existing anti-slip ceramic tiles, it has outstanding substantial characteristics and significant progress; and the particle size of the anti-slip particles is also smaller, and the anti-slip microstructure formed is more delicate, which can not only produce a greater anti-slip effect on the human foot, but also has a better anti-slip effect on the surface of the ceramic tile product. The adsorption area is increased, the anti-slip performance of the ceramic tile products is improved, and the dirt is not easy to hide. The ceramic tile products are easy to clean and have very good anti-fouling ability and easy-to-clean performance. In addition, the fineness of the transparent glaze slurry is controlled to be 0.2% to 0.5% by weight of the 325-mesh sieve residue. The conventional surface glaze fineness is generally less than 1% of the 325-mesh sieve residue. The fineness of the glaze slurry of the glaze surface of the present application is finer, so that the fusibility is stronger during firing, which not only helps to reduce the firing temperature, but also can form a smoother and flatter glaze layer on the surface of the green body and the anti-slip particles, making it difficult for dirt to penetrate or adhere to the ceramic, thereby improving the anti-fouling ability of the ceramic tile products and solving the problems of dirt absorption and sticking of the ceramic tile products. At the same time, the transparent glaze can also adhere more closely to the green body, thereby improving the quality of the glaze layer, making the glaze layer not easy to be knocked off, and improving its durability.
[0017] The ceramic tile product provided by the present invention has excellent anti-slip and anti-fouling properties. Its anti-slip performance is greater than or equal to R11, the wet static friction coefficient is greater than or equal to 0.78, the wet anti-slip value is greater than or equal to 60, and the stain resistance level is greater than or equal to 5. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic diagram of the production process of the present invention. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is clearly and completely described below in conjunction with the specific implementation methods of the present invention.
[0020] The present invention provides a method for preparing anti-skid and anti-fouling ceramic tiles, comprising mixing anti-skid particles with transparent glaze slurry to form an anti-skid glaze, and then applying the anti-skid glaze on the surface of a ceramic tile body. In order to achieve the purpose proposed by the present invention: the ball-milling fineness of the transparent glaze slurry is 0.3% to 0.5% by weight of the residue on a 325-mesh sieve, and the particle grading of the anti-skid particles is calculated in weight percentage as follows: less than 0.5% on an 80-mesh sieve, 30% to 35% on a 100-mesh sieve, 75% to 80% on a 120-mesh sieve, and 95% to 98% on a 250-mesh sieve. In this way, through the particle grading of the above-mentioned anti-slip particles, anti-slip particles of different sizes are combined with transparent glaze, thereby forming an anti-slip texture glaze effect of different sizes and unevenness on the surface of the ceramic tile product, thereby increasing the friction coefficient of the surface of the ceramic tile product and enhancing its anti-slip performance; and through the control of particle grading, the size distribution of anti-slip particles produced in different batches is more consistent, thereby ensuring that the anti-slip texture distribution of ceramic tile products produced in each batch is also more consistent, thereby ensuring that all ceramic tile products have excellent anti-slip performance. In addition, the ball-milling fineness of conventional transparent glaze slurry is 325, and the weight percentage of the sieve residue is less than 1%. The ball-milling fineness of the transparent glaze slurry of the present application is smaller than that of the conventional transparent glaze slurry, which makes the transparent glaze of the present application more fusible during firing, thereby helping to reduce the firing temperature and form a smoother and flatter glaze layer on the surface of the green body, thereby greatly reducing the number of micropores on the surface of the ceramic tile product, improving its anti-fouling ability, and solving the problems of dirt absorption and dirt sticking of the ceramic tile product; and due to the protection of the transparent glaze, the anti-slip particles are not easily knocked off during use, so that the anti-slip performance can be maintained for a long time; in addition, after firing, the ceramic tile product also needs to be ground and polished to achieve a smooth texture. The transparent glaze in the present application can form a smoother and flatter glaze layer on the surface of the ceramic tile product, thereby greatly reducing the workload of grinding and polishing, and further reducing production costs.
[0021] In the present application, since the anti-skid particles are mixed into the transparent glaze slurry to form the anti-skid glaze, during the glazing process, the anti-skid particles will not accumulate on a certain area of the body, but will be evenly dispersed on the surface of the ceramic tile body, thereby greatly improving the effective utilization rate of the anti-skid particles and reducing the amount of anti-skid particles used; in addition, different application occasions have different requirements for the anti-skid performance of ceramic tile products. For example, for hospitals and shopping malls with large traffic, the anti-skid performance requirements are relatively high, and for ordinary family kitchens and toilets, the anti-skid performance requirements are relatively low. Therefore, for ceramic tile products with different anti-skid requirements, the amount of anti-skid particles added to the transparent glaze slurry is also different, generally 12% to 20% by weight (i.e., 12 to 20 kg of anti-skid particles are added to 100 kg of transparent glaze slurry).
[0022] The chemical composition of the transparent glaze slurry in the present application is calculated by weight percentage: Al2O3 content 16% to 25%, SiO2 content 45% to 55%, CaO content 3% to 8%, MgO content 1% to 2%, ZnO content 2% to 3%, BaO content 2% to 4%, K2O content 1% to 2%, Na2O content 6% to 12%, and ignition loss 8% to 13%. In specific implementation, the existing transparent glaze finished product can be purchased and then mixed with pure chemical raw materials to obtain the above chemical composition; when grinding the transparent glaze slurry, the various raw materials of the transparent glaze are mixed together and put into a ball mill with water in a certain proportion, and additives such as sodium tripolyphosphate and sodium carboxymethyl cellulose are added to increase the fluidity of the glaze slurry. Through the above-mentioned ratio and the control of the ball-milling fineness of the transparent glaze slurry, the transparent glaze of the present application has very good meltability during firing, so that the molten surface glaze can be spread on the surface of the ceramic tile body into a very smooth glaze surface, thereby greatly reducing the amount of glaze used. Therefore, the amount of anti-slip glaze slurry used on the ceramic tile body is 63 to 72 g / ㎡, which is much lower than the amount of anti-slip glaze slurry used in other anti-slip ceramic tile products; since transparent glaze and anti-slip particles are relatively expensive, this can greatly reduce production costs.
[0023] The chemical composition of the anti-slip particles is calculated by weight percentage: Al2O3 content 8% to 18%, SiO2 content 50% to 65%, CaO content 6% to 18%, MgO content 5% to 12%, ZnO content 2% to 5%, BaO content 4% to 10%, K2O content 5% to 10%; the sum of all chemical components is 100%. In this way, the melting temperature of the anti-slip particles is greater than or equal to 1200°C, so that the anti-slip particles do not melt or partially melt during firing and combine with the transparent glaze to form an anti-slip texture glaze effect of varying sizes and unevenness on the surface of the ceramic tile product. The raw materials of the anti-slip particles can be configured using chemical raw materials, or they can be configured using minerals such as quartz and feldspar in combination with chemical raw materials.
[0024] When the raw material of the green body is ball-milled, the fineness of the slurry obtained by ball milling is 0.8% to 1.0% by weight of the residue on a 250-mesh sieve. In this way, the particle distribution of the green body is very uniform, and the density and strength of the green body are also high, thereby reducing the shrinkage rate of the green body during the firing process; in this way, during the firing process, the shrinkage of the anti-slip glaze is more matched with the shrinkage rate of the green body, and the combination of the two is more firm, thereby effectively preventing the glaze from cracking or peeling, so that the anti-slip glaze forms a uniformly distributed and smooth glaze on the surface of the ceramic tile green body, and dirt is not easy to adhere to the surface of the ceramic tile product, which helps to improve the anti-fouling performance of the ceramic tile product.
[0025] In order to further ensure the mechanical strength of the anti-slip ceramic tile and improve the adaptability between the body and the anti-slip glaze, so that the anti-slip glaze is tightly combined with the body without cracking or peeling. The chemical composition of the ceramic tile body is calculated by weight percentage: Al2O3 content 18% to 21%, SiO2 content 60% to 74%, CaO content 0.1% to 0.5%, MgO content 0.7% to 1.4%, Fe2O3 content 0.3% to 0.7%, TiO2 content 0.1% to 0.5%, K2O content 1% to 3%, Na2O content 2% to 4%, and the sum of all chemical components is 100%. In this way, the contents of Al2O3 and SiO2 in the green body and the transparent glaze are relatively close, and more mullite crystals are easily generated between the glaze layer and the green body layer during the firing process to embed the two together, thereby making the bond between the glaze layer and the green body more firmly, making the anti-slip glaze layer not easily knocked off during use, and thus having better durability.
[0026] The slurry obtained by ball milling is subjected to powder spraying to obtain a powder material whose particle size distribution is calculated by weight percentage: less than 0.5% of the material on the 20-mesh screen, and 70% to 85% of the material on the 60-mesh screen. In this way, the powder material has a good molding ability when being pressed and formed, and can be pressed into a green body with high strength and uniform density, so that the fired ceramic tile product has good mechanical strength and improves its durability.
[0027] The powder is fed into a press and pressed into a ceramic tile body. The pressing pressure of the press is 310±10 bar, and the number of single-machine pressings is 3.5-4.0 times / minute. The dry strength of the obtained ceramic tile body is greater than 0.8MPa. This can make the fired ceramic tile product have better strength, thereby improving its durability.
[0028] The present application sends the ceramic tile blank with anti-skid glaze applied on the surface into the kiln for firing, adopts a one-time firing process, and the firing time is 45 to 55 minutes; the firing curve is: the first stage is heated from room temperature to 900°C, and the heating time is 5 to 10 minutes; the second stage is heated from 900°C to 1200°C, and the heating time is 13 to 17 minutes; then it is kept at 1200°C for 10 to 15 minutes; after the insulation is completed, it is cooled from 1200°C to 900°C, and the cooling time is 2 to 3 minutes; then it is cooled from 900°C to room temperature, and the cooling time is 5 to 10 minutes. In this way, by controlling the temperature and time parameters, the shrinkage rate of the anti-skid glaze and the ceramic tile blank during the firing process is kept consistent, thereby effectively avoiding the occurrence of glaze layer defects, so that the anti-skid glaze and the ceramic tile blank are closely combined to form a strong ceramic tile product with excellent anti-skid performance; at the same time, it can also reduce the firing scrap rate, thereby saving production costs.
[0029] Through the above-mentioned preparation method, the present invention also provides a non-slip and anti-fouling ceramic tile product, the anti-slip performance of the ceramic tile product is greater than or equal to R11, the wet static friction coefficient is greater than or equal to 0.78, the wet anti-slip value is greater than or equal to 60, and the stain resistance level is greater than or equal to 5. It has very excellent non-slip and anti-fouling properties.
[0030] The technical points and technical effects of the present invention are further described below through specific examples and comparative examples.
[0031] Embodiment 1:
[0032] A method for preparing a non-slip and anti-fouling ceramic tile, such as Figure 1 As shown, the preparation steps include:
[0033] S1: Sending ceramic tile body raw materials into a ball mill for ball milling, the weight percentage of each chemical composition in the ceramic tile body raw materials is: Al2O3 content 18%~21%, SiO2 content 60%~74%, CaO content 0.1%~0.5%, MgO content 0.7%~1.4%, Fe2O3 content 0.3%~0.7%, TiO2 content 0.1%~0.5%, K2O content 1%~3%, Na2O content 2%~4%, and the sum of all chemical components is 100%. In this embodiment, the following mineral raw materials are used for configuration: 15 parts of sodium potassium sand, 9 parts of Xi'an sand, 5 parts of potassium sand, 18 parts of potassium sand, 19 parts of potassium sodium sand, 7 parts of potassium sodium sand, 5 parts of high clay, 2 parts of talcum mud, 6 parts of Guangbai mud, and 14 parts of washed high-alumina mud; the above raw materials are ball-milled to obtain a slurry with a fineness of 0.8% to 1.0% by weight of the residue on a 250-mesh sieve;
[0034] S2: The slurry obtained by ball milling is aged, toned, and powdered to obtain a powder whose particle size distribution is as follows: less than 0.5% of the material on a 20-mesh sieve and 70% to 85% of the material on a 60-mesh sieve; the slurry aging time in this step is greater than 24 hours;
[0035] S3: feeding the powder into a press to press into a ceramic tile body, wherein the pressing pressure of the press is 310±10 bar, and the number of single-machine pressing times is 3.5 to 4.0 times / minute; after drying, the obtained ceramic tile body has a dry strength greater than 0.8 MPa;
[0036] S4: Apply the prepared anti-skid glaze to the dried ceramic tile body; the anti-skid glaze is made by mixing transparent glaze slurry and anti-skid particles evenly; the raw materials of the transparent glaze are mixed with 97 parts of KG4082 glaze (which can be purchased from Guangdong Sanshui Dahong Glaze Co., Ltd.) and 3 parts of aluminum oxide according to the weight ratio, and the ratio of the transparent glaze raw material to water is 2:1, and 0.3% of carboxymethyl cellulose and 0.2% of sodium tripolyphosphate by weight of the transparent glaze raw material are added; after the above mixture is ground in a ball mill, it is sieved to remove iron to obtain a transparent glaze slurry with a ball mill fineness of 0.3% to 0.5% by weight of the residue on a 325 mesh sieve, and then the ground anti-skid particles are added to the transparent glaze slurry and mixed evenly to obtain the anti-skid glaze, and the density of the anti-skid glaze is 1.25g / cm 3 ; In this embodiment, the amount of anti-slip particles added to the transparent glaze slurry is 12wt% by weight (that is, 12 parts of anti-slip particles are added to 100 parts of transparent glaze slurry); the chemical composition of the transparent glaze slurry is as follows by weight: Al2O3 content 20%, SiO2 content 50%, CaO content 4%, MgO content 1.5%, ZnO content 2%, BaO content 2.5%, K2O content 1.5%, Na2O content 7%, loss on ignition 11.5%; the chemical composition of the anti-slip particles is as follows by weight: Al2O3 content 16%, SiO2 content 52%, CaO content 7%, MgO content 7%, ZnO content 4%, BaO content 6%, K2O content 8%; the melting temperature of the anti-slip particles is 1210℃; the amount of anti-slip glaze applied to the surface of the ceramic tile body is 65g / ㎡.
[0037] S5: The ceramic tile body with anti-slip glaze applied on the surface is sent into the kiln for firing, using a one-time firing process, and the firing time is 45 to 55 minutes; the firing curve is: the first stage is from room temperature to 900°C, and the heating time is 5 to 10 minutes; the second stage is from 900°C to 1200°C, and the heating time is 13 to 17 minutes; then it is kept at 1200°C for 10 to 15 minutes; after the insulation is completed, it is cooled from 1200°C to 900°C, and the cooling time is 2 to 3 minutes; then it is cooled from 900°C to room temperature, and the cooling time is 5 to 10 minutes.
[0038] S6: After firing, the ceramic tile products are polished, cleaned, packed and put into storage.
[0039] Embodiment 2:
[0040] The steps and parameters in this embodiment are the same as those in Embodiment 1, except that in this embodiment, the amount of anti-slip particles added to the transparent glaze slurry is 18 wt % (ie, 18 parts of anti-slip particles are added to 100 parts of transparent glaze slurry).
[0041] Comparative Example:
[0042] This embodiment is a comparative example, and each step and parameter are the same as those of the first embodiment, except that in this embodiment, no anti-slip particles are added to the transparent glaze slurry, and the amount of the transparent glaze slurry applied to the surface of the ceramic tile body is 65 g / ㎡.
[0043] The ceramic tile products prepared in Examples 1, 2 and Comparative Example were tested for performance, and the test results are shown in the following table:
[0044]
[0045]
[0046] Through the comparison of the above test data, it can be seen that ceramic tile products without adding anti-slip particles also have very good pollution resistance, but their anti-slip performance is poor. This is because transparent glaze can form a smooth and flat glaze layer on the surface of the ceramic tile, making it difficult for dirt to adhere and hide. Therefore, it has very good pollution resistance, but its surface is too smooth, resulting in poor anti-slip performance.
[0047] As the amount of anti-slip particles increases, the anti-slip performance of ceramic tile products also increases. This is because more anti-slip particles can form more anti-slip concave and convex textures on the surface of ceramic tile products, thereby increasing their friction coefficient and improving their anti-slip performance. Therefore, in actual production, different proportions of anti-slip particles can be added according to different usage scenarios to meet the requirements of ceramic tiles for anti-slip performance in different occasions.
[0048] In addition, since the particle size of the anti-slip particles is very small, the size of the anti-slip concave and convex texture formed is also small, and the glaze surface formed by the transparent glaze is very smooth, so the glaze surface of the entire ceramic tile product is relatively smooth and flat, and dirt is not easy to hide or adhere to these anti-slip concave and convex textures, which makes the ceramic tile product have better anti-fouling properties and easy to clean.
[0049] It can be seen that the ceramic tile product of the present invention prepared by the above-mentioned preparation method can form an anti-skid and anti-fouling layer on the surface of the green body layer, and the anti-skid and anti-fouling layer has an anti-skid performance greater than or equal to R11, a wet static friction coefficient greater than or equal to 0.78, a wet anti-slip value greater than or equal to 60, and a stain resistance grade greater than or equal to 5. This makes the ceramic tile product of the present invention have very good anti-skid performance and very good anti-fouling performance.
Claims
1. A method for preparing a non-slip and anti-fouling ceramic tile, comprising mixing non-slip particles with a transparent glaze slurry to prepare a non-slip glaze, and then applying the non-slip glaze to the surface of the ceramic tile body, characterized in that: The ball-milling fineness of the transparent glaze slurry is 0.3% to 0.5% by weight of the residue on the 325-mesh sieve, and the particle grading of the anti-slip particles is as follows in weight percentage: less than 0.5% on the 80-mesh sieve, 30% to 35% on the 100-mesh sieve, 75% to 80% on the 120-mesh sieve, and 95% to 98% on the 250-mesh sieve.
2. The method for preparing the anti-slip and anti-fouling ceramic tile according to claim 1, characterized in that: The amount of the anti-slip particles added to the transparent glaze slurry is 12% to 20% by weight.
3. The method for preparing the anti-slip and anti-fouling ceramic tile according to claim 1, characterized in that: The chemical composition of the transparent glaze slurry is calculated in weight percentage as follows: Al2O3 content 16% to 25%, SiO2 content 45% to 55%, CaO content 3% to 8%, MgO content 1% to 2%, ZnO content 2% to 3%, BaO content 2% to 4%, K2O content 1% to 2%, Na2O content 6% to 12%, and loss on ignition 8% to 13%.
4. The method for preparing the anti-slip and anti-fouling ceramic tile according to claim 3, characterized in that: The chemical composition of the anti-slip particles is calculated in weight percentage as follows: Al2O3 content 8% to 18%, SiO2 content 50% to 65%, CaO content 6% to 18%, MgO content 5% to 12%, ZnO content 2% to 5%, BaO content 4% to 10%, K2O content 5% to 10%; the melting temperature of the anti-slip particles is greater than or equal to 1200°C.
5. The method for preparing the anti-slip and anti-fouling ceramic tile according to claim 1, characterized in that: The usage amount of the anti-slip glaze slurry on the ceramic tile body is 63-72 g / ㎡.
6. The method for preparing the anti-slip and anti-fouling ceramic tile according to claim 5, characterized in that: The chemical composition of the ceramic tile body is calculated in weight percentage as follows: Al2O3 content is 18% to 21%, SiO2 content is 60% to 74%, CaO content is 0.1% to 0.5%, MgO content is 0.7% to 1.4%, Fe2O3 content is 0.3% to 0.7%, TiO2 content is 0.1% to 0.5%, K2O content is 1% to 3%, and Na2O content is 2% to 4%.
7. The method for preparing the anti-slip and anti-fouling ceramic tile according to claim 6, characterized in that: The slurry obtained by ball milling is subjected to powder spraying to obtain a powder material, and the particle size distribution of the powder material is as follows: less than 0.5% of the material on a 20-mesh sieve, and 70% to 85% of the material on a 60-mesh sieve.
8. The method for preparing the anti-slip and anti-fouling ceramic tile according to claim 7, characterized in that: The powder is fed into a press and pressed into a ceramic tile body. The pressing pressure of the press is 310±10 bar, and the number of single-machine pressings is 3.5 to 4.0 times per minute. The dry strength of the obtained ceramic tile body is greater than 0.8 MPa.
9. The method for preparing the anti-slip and anti-fouling ceramic tile according to claim 8, characterized in that: The ceramic tile body with anti-slip glaze applied on the surface is sent into the kiln for firing, using a one-time firing process and a firing time of 45 to 55 minutes; the firing curve is: the first stage is from room temperature to 900°C, and the heating time is 5 to 10 minutes; the second stage is from 900°C to 1200°C, and the heating time is 13 to 17 minutes; then it is kept at 1200°C for 10 to 15 minutes; after the insulation is completed, it is cooled from 1200°C to 900°C, and the cooling time is 2 to 3 minutes; then it is cooled from 900°C to room temperature, and the cooling time is 5 to 10 minutes.
10. A ceramic tile product obtained by the method for preparing a non-slip and anti-fouling ceramic tile according to any one of claims 1 to 9, characterized in that: The invention comprises a blank and an anti-skid and anti-fouling layer on the surface of the blank. The anti-skid and anti-fouling layer has an anti-skid performance greater than or equal to R11, a wet static friction coefficient greater than or equal to 0.78, a wet anti-skid value greater than or equal to 60, and a stain resistance grade greater than or equal to 5.
Citation Information
Patent Citations
Ceramic tile with dry particle glaze-decorated surface and manufacturing method thereof
CN103626523A
Wear-resistant and non-slip ceramic tile and preparation method thereof
CN107382373A
Anti-skid glaze and anti-skid floor tile
CN108706874A
Preparation method of antiskid and antifouling glazed tile and prepared antiskid and antifouling glazed tile
CN111217623A
Anti-skid ceramic tile with fine and smooth texture glaze and preparation method of anti-skid ceramic tile
CN114573374A